Silencing of prophenoloxidase (proPO) gene in freshwater prawn, Macrobrachium rosenbergii, makes them susceptible to white spot syndrome virus (WSSV). Issue 5 (10th November 2020) - Thamizhvanan, S.; Nafeez Ahmed, A.; Vinoth Kumar, D.; Vimal, S.; Majeed, S. Abdul; Taju, G.; Hauton, Chris; Sahul Hameed, A. S.
Abstract: Prophenoloxidase (proPO) is very important to protect the invertebrates from microbial infections. Our previous studies revealed that proPO was up‐regulated in WSSV‐injected Macrobrachium rosenbergii and is responsible for protecting M. rosenbergii from WSSV. In order to prove this mechanism, an attempt was made in the present study to silence the proPO gene in freshwater prawn by injection of dsRNA‐proPO followed by WSSV challenge. Two partial fragments of proPO with the size of 251 and 331 bp were used to synthesize dsRNA using LITMUS38i vector and E. coli . The bacterially synthesized dsRNA‐proPO was used to silence proPO gene to determine its involvement in developing resistance in prawn against WSSV. In proPO gene‐silenced prawn, 100% mortality was observed after WSSV challenge whereas no mortality was observed in prawn injected with WSSV alone. The WSSV infection in gene‐silenced prawn was confirmed by PCR, and its propagation was quantified by ELISA and real‐time PCR at different time intervals. Real‐time PCR assay revealed a significant reduction in the expression of proPO gene in WSSV‐challenged proPO‐silenced prawn when compared to normal prawn. Level of proPO was reduced significantly in the haemolymph of proPO‐silenced prawn when compared to prawn injected with PBS.